2020
DOI: 10.1111/1747-0080.12606
|View full text |Cite
|
Sign up to set email alerts
|

Electronic food records among middle‐aged and older people: A comparison of self‐reported and dietitian‐assisted information

Abstract: Aim Nutrition‐based applications (“apps”) offer enormous research potential, however evidence of their use and acceptability among older adults is limited. We compared self‐reported and dietitian‐adjusted dietary intake records among adults aged 55 to 75 years using the Research Food Diary (RFD) app. Methods Participants were recruited from the 45 and Up Study and completed a 3‐day food record using the RFD. A follow‐up dietetic telephone interview was performed to confirm the electronic dietary data. Independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…22 A recent Australian study also found that applying informed data cleaning adjustments to participants' self-reported records was as accurate as dietitians interviewing participants to correct implausible entries and fill missing data and far less time-consuming. 22 Applying methods such as these could improve the accuracy of data collected in research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A recent Australian study also found that applying informed data cleaning adjustments to participants' self-reported records was as accurate as dietitians interviewing participants to correct implausible entries and fill missing data and far less time-consuming. 22 Applying methods such as these could improve the accuracy of data collected in research.…”
Section: Discussionmentioning
confidence: 99%
“…When selecting the length of each administration, a balance needs to be found between learning to use the platform and fatigue from recording intake daily. Future studies may benefit from including a familiarization period, giving participants time to learn how to navigate the platform and record intake before the data are used for research 22. A recent Australian study also found that applying informed data cleaning adjustments to participants' self-reported records was as accurate as dietitians interviewing participants to correct implausible entries and fill missing data and far less time-consuming 22.…”
Section: Discussionmentioning
confidence: 99%
“…Further, clear and detailed reporting of dietary study methods are needed to allow readers to draw appropriate conclusions. The articles in this issue by Clarke and colleagues 5 and Lancaster and colleagues 6 in particular, exemplify best practice in the description of dietary assessment methods. Both papers included a description of the measurement techniques in sufficient detail that they could be replicated, and clearly acknowledged methodological limitations.…”
mentioning
confidence: 99%
“…The increased technical literacy of the population and the advances in dietary assessment applications (apps) have moved the assessment of dietary intake from requiring the expertise of dietitians and nutritionists to consumers. The article by Lancaster and colleagues 6 further advances the science and practice of assessing dietary intake by studying the accuracy of dietary assessment in a food diary app by people 55‐75 years of age. Participants kept a 3‐day food record in an app and were interviewed to confirm their data.…”
mentioning
confidence: 99%
“…Computer applications on smartphones and tablets have resulted in less participant burden in collecting nutrition information; however, nutrition expertise is still required in determining random and systematic error. Lancaster et al 12 compared self‐reported and dietitian‐adjusted dietary intake records among older adults using the Research Food Diary app. Significant errors of up to 8% occurred in some nutrients and food groups between the self‐reported and dietitian‐assisted records; however, none between the dietitian‐assisted and carefully applied dietetic assumptions used independently to adjust the self‐reported records.…”
mentioning
confidence: 99%